PERTANGGUNGJAWABAN KEPALA DESA TERHADAP MALADMINISTRASI PENDATAAN TANAH GIRIK DI BUKU LETTER C DESA LEUWINANGGUNG - Andi Abdul Kahar (2023)
The Village Government has the role of providing services to the community who wish to register their land for the first time by providing preliminary evidence in the form of a copy of letter C. This study examines how legal protection for owners of land rights has not been registered over the Village Government administration mall, as well as the responsibilities of the Village Government in terms of letter C maladministration occurs, causing losses to owners of unregistered land rights. This research was conducted using a normative juridical approach. The research specifications are analytical descriptive in nature, then analyzed qualitatively. Theoretically there is no legal protection for owners of unregistered land rights because in principle land registration regulated in legislation aims to provide legal protection and create legal certainty, but in practice owners of land rights who feel their rights have been violated can file objections or lawsuits. , and the Village Government who are proven to have committed administrative malfeasance may be subject to a position sanction determined by the Regent.